1998
DOI: 10.1055/s-0037-1614240
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of vWF Inhibits both Injury Induced Arterial and Venous Thrombosis in the Hamster

Abstract: Summaryvon Willebrand factor (vWF) is instrumental in arterial but has also been implicated in venous thrombogenesis. To address its role in venous thrombosis, experimental thrombosis was induced in the carotid artery and the femoral vein of hamsters, following which thrombus prevention by two different antagonists of vWF was studied. The first antagonist was the anti-human vWF monoclonal antibody AJvW-2, which inhibits the botrocetin and ristocetin induced aggregation of human blood platelets. AJvW-2 reacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 32 publications
(45 reference statements)
2
45
0
Order By: Relevance
“…In general, in flow chambers a more effective inhibition with vWF-GPIb inhibitors is obtained at higher shear rates, 11,12,36 which we also demonstrated here by finding a more pronounced effect of 6B4 on platelet adhesion to collagen when a higher shear was applied in a flow chamber; also, in vivo an arterial thrombus was more readily prevented than a venous one. 11 This implies that inhibition of GPIb would result especially in arterial effects, which in addition could result in less bleeding risk.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In general, in flow chambers a more effective inhibition with vWF-GPIb inhibitors is obtained at higher shear rates, 11,12,36 which we also demonstrated here by finding a more pronounced effect of 6B4 on platelet adhesion to collagen when a higher shear was applied in a flow chamber; also, in vivo an arterial thrombus was more readily prevented than a venous one. 11 This implies that inhibition of GPIb would result especially in arterial effects, which in addition could result in less bleeding risk.…”
Section: Discussionsupporting
confidence: 82%
“…This finding supports data obtained with other GPIb-vWF-blocking agents (VCL, anti-vWF MoAb AJvW-2) that lengthened the bleeding time only moderately. 11,12,17,18 This finding is important and might provide a major advantage in the development of antithrombotic agents compared with GPIIb-IIIa antagonists, like ReoPro. 37 On the other hand, the GPIb-vWF interaction in contrast to the GPIIb-IIIa-fibrinogen interaction is the ultimate first step in platelet adhesion under fast blood flow.…”
Section: Discussionmentioning
confidence: 97%
“…Our finding is consistent with another in vivo study where, in a crushed femoral vein model (hamster), it was shown that the presence of an antagonist to the VWF A1 domain decreased thrombus size. 29 The key finding in our study is the essential role for VWF in forming an occlusive thrombus under venous flow conditions. The importance of VWF in occlusive thrombus formation at arterial shear conditions has been shown in vivo.…”
Section: Role Of Vwf In Venous Thrombosis 2427mentioning
confidence: 59%
“…AJvW-2 is a murine MoAb that recognizes a conformational epitope of the A1 domain of vWF involved in its binding to platelet GPIb. 12,33 AJvW-2 has been shown to specifically inhibit platelet adhesion and aggregation under conditions of high shear stress by blocking the interaction between vWF and GPIb. 12,33 Our finding that AJvW-2 completely inhibits the high shear-induced platelet aggregation in the blood from patients with a very acute phase of ACSs, as well as recent demonstrations that the vWF-GPIb interaction is essential during coronary occlusion and that inhibition of vWF binding to GPIb can prevent coronary thrombosis 7,[33][34][35][36] and further restenosis after vascular injury, 36,37 suggests that AJvW-2, if administered after coronary interventions (eg, angioplasty, stenting, or atherectomy), may prevent new events in the coronary arteries and inhibit restenosis.…”
Section: Discussionmentioning
confidence: 99%